Elevated D-dimer on admission may predict poor prognosis in childhood influenza associated encephalopathy - Huizhen Wang; Lingkong Zeng; Xingfeng Cheng; Hui Li; Hong Zhang; Yuanmei Shi; Yong Zhang; Changjian Li (Scientific Reports)
Abstract To determine the risk factors for poor prognosis of influenza-associated encephalopathy (IAE), 56 eligible children with IAE who were treated in the pediatric intensive care unit of Wuhan Children’s Hospital from January 2022 to December 2023 were selected for retrospective analysis and grouped according to poor prognosis or not, and independent risk factors for poor prognosis were found by regression analysis. Results showed 26 children (26/30, 46.4%) had a poor prognosis. In the univariate analysis, the poor prognosis group compared with the clinically cured group showed a significant increase in the number of days of hospitalization (3.0 vs. 9.5 days, P < 0.001), high-sensitivity C-reactive protein (6.80 vs. 1.88 mg/L, P = 0.003), interleukin-6 (20.26 vs. 8.24 pg/mL, P = 0.001), interleukin-10 (11.75 vs. 4.72 pg/mL, P = 0.003), alanine aminotransferase (104.0 vs. 20.0 U/L, P = 0.011), aspartate azelotransferase (186.5 vs. 37.0 U/L, P = 0.003), serum albumin (37.99 vs. 40.76 g/L, P = 0.042), prothrombin time (13.2 vs. 11.4 s, P = 0.017), D-dimer (4.34 vs. 0.44 mg/L FEU, P < 0.001), peripheral blood CD19 B-cell count (35.11 vs. 32.75 cells/µL, P = 0.018), and cerebrospinal fluid chloride (126.82 vs. 125.50 mmol/L, P = 0.027) were statistically different in the above 11 indicators. After binary logistic regression analysis, it was concluded that D-dimer was an independent risk factor for poor prognosis (odds ratio = 1.440, 95% confidence interval 1.052–1.972, P = 0.023), and the area under the curve (95% confidence interval) was 0.802 (0.680–0.924), P < 0.001. When D-dimer was ≥ 1.18 mg/L FEU, the occurrence of poor prognosis was predicted with sensitivity and specificity of 65.4% and 96.7%, respectively. In conclusion, IAE has a high incidence of poor prognosis, in which D-dimer is a possible risk factor with discriminatory value in assessing the occurrence of poor prognosis. However, due to the limitations of retrospective single-center small sample size data, more confirmation from multicenter large sample size studies is needed in the future.